Modeling the Interaction between the Isoniazid Anti-Tuberculosis Drug and Functionalized Carbon Nanotubes for Medical Applications: A Quantum Chemical Study - Mohadese Moradi; Shahla Hamedani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2024)
Introduction: The purpose of using nano-carriers for drugs delivery, such as nanotubes, was slow release of drug and reducing side effects of drugs. Drugs are very active due to their many functional groups. Therefore, reactivity of drug is reduced by being in nanotube field due to electronic resonance of drug with nanotube and it stays longer in body. The present study aimed to investigate the interaction of isoniazid with functionalized single-walled carbon nanotubes. Methods: In the present theoretical study, considering the importance of isoniazid as the first line of treatment for tuberculosis disease, the performance of carbon nanostructures for adsorption of isoniazid was evaluated using quantum computation. Using density functional theory at theoretical level of B3LYP/6-31G** structure of drug and f-SWCNT and nano-drug complexes were optimized. Results: Effect of adsorption on the electronic properties and stability of the nanotube was also examined. In this regard, for different configurations, the strength and nature of intermolecular interactions were evaluated by energy parameters and molecular orbitals. Based on the obtained results, a specific configuration displayed the most negative adsorption energy and enthalpy, establishing itself as the most stable structure among the various configurations. Conclusion: Results showed that the electron density of the HOMO (Highest Occupied Molecular Orbital) was localized on the nanotube, while the electron density of the LUMO (Lowest Unoccupied Molecular Orbital) was situated on the drug molecule. The energy gap between two molecular orbitals increased due to the adsorption process; changes lead to an increase in the electrical conductivity of the complex following adsorption. According to the natural bond orbitals, results, the isoniazid molecule and functionalized single-walled carbon nanotube act as both electron donor and acceptor in the complex. Analysis of the results obtained from quantum theory of atoms in molecules, showed the intermolecular interaction between the drug and the functional group of the nanotube has been established, the most important of which is the hydrogen bond. Finally, the findings showed that functionalized SWCNTs can be acted as a drug carrier for isoniazid anti-tuberculosis drug.